Invertebrate community response to coarse woody debris removal for bioenergy production from intensively managed forests. Issue 1 (11th December 2017) - Grodsky, Steven M.; Moorman, Christopher E.; Fritts, Sarah R.; Campbell, Joshua W.; Sorenson, Clyde E.; Bertone, Matthew A.; Castleberry, Steven B.; Wigley, T. Bently
Abstract: Increased market viability of harvest residues as forest bioenergy feedstock may escalate removal of coarse woody debris in managed forests. Meanwhile, many forest invertebrates use coarse woody debris for cover, food, and reproduction. Few studies have explicitly addressed effects of operational‐scale woody biomass harvesting on invertebrates following clearcutting. Therefore, we measured invertebrate community response to large‐scale harvest residue removal and micro‐site manipulations of harvest residue availability in recently clearcut, intensively managed loblolly pine ( Pinus taeda ) forests in North Carolina (NC; n = 4) and Georgia (GA; n = 4), USA. We captured 39, 794 surface‐active invertebrates representing 171 taxonomic groups using pitfall traps situated among micro‐site locations (i.e., purposefully retained piles of hardwood stems and piles of conifer stems and areas without coarse woody debris in NC; windrows and no windrows in GA). Micro‐site locations were located within six, large‐scale treatments (7.16–14.3 ha) in clearcuts. Large‐scale treatments represented intensive harvest residue removal, 15% and 30% harvest residue retention, and no harvest residue removal. In NC, ground beetles (Coleoptera: Carabidae) and crickets (Orthoptera: Gryllidae) were three times more abundant in treatments with no harvest residue removal than those with the most intensive harvest residue removal and were reduced in treatments that retained 15% or 30% of harvest residues, although not significantly. Invertebrate taxa richness was greater at micro‐site locations with retained hardwood and pine ( Pinus spp.) harvest residues than those with minimal amounts of coarse woody debris. In both states, relative abundances of several invertebrate taxa, including cave crickets (Orthoptera: Rhaphidophoridae), fungus gnats (Diptera: Mycetophilidae and Sciaridae), millipedes (Diplopoda), and wood roaches (Blattodea: Ectobiidae), were greater at micro‐site locations with retained harvest residues than those with minimal coarse woody debris. Intensified woody biomass harvesting without retention of ≥15% of harvest residue volume may reduce invertebrate taxa richness and abundances of some key invertebrate taxa in regenerating stands. Further, harvest residue management during and after woody biomass harvesting may be an important consideration for maintaining invertebrate diversity and conserving invertebrates that are influential in the maintenance of ecosystem function and integrity in young forests.